Success of Extracorporeal Shockwave Lithotripsy (ESWL) in Relation to Triple D Score - Bazgha Hassan, Shariq Bin Yousuf, Laraib Gul, Shuah Ullah, Harris Hassan Qureshi, Naveed Ahmed Mahar, Altaf Hashmi (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the frequency of success of ESWL in patients with renal stones and to compare the success of ESWL with different Triple D scores in the same group of patients. Methodology: Descriptive study in the Department of Urology, Sindh Institute of Urology and Transplantation Hospital, Karachi from 29thOctober 2020 to 28th April 2020. One hundred and fifteen patients with renal stone seen as radio opaque shadow on X rays KUB were included. CT was performed and stone diameters were measured. Quadruple D-score was defied because stone location is combined with TrD-S ranging from 0 (worst) to 3 (best) points. KUB was used for evaluation of stone free status after 4-weeks of ESWL sessions. Patient can be regarded stone free if complete stone was removed. Results: The mean age was 48.99±10.67 years, the mean size of the stone was 12.99±3.54mm, and the mean triple D score was 1.70±1.00. There were 75(65.22%) males and 40(34.78%) female patients. The success of ESWL was found in 79(68.70%) patients. On comparison of success of ESWL with triple D score, success of ESWL was found in 04(26.7%) having 0 score, in 19(54.3%) having 01 score, in 27(77.1%) having 02 score, and in 29 (96.7%) having 03 score (P<0.001). Conclusion: The triple D score appears to be a useful predictor of ESWL treatment outcomes. Using the Triple D score may improve the cost-effectiveness of ESWL by limiting its use to patients likely to have favourable outcomes. Key Words: Extracorporeal shockwave lithotripsy (ESWL), Triple D score, Renal stone